Experience Lived by Iranian Patients with Irritable Bowel Syndrome: Transitory Crisis and Liberation - Mohebbi, Zinat; Sharif, Farkhondeh; Peyrovi, Hamid; Rakhshan, Mahnaz; Naini, Mahvash Alizade; Zarshenas, Ladan (Investigación y Educación en Enfermería, 2019)
Objective. Research on the nature of living with Irritable Bowel Syndrome. Methods. Qualitative study of the hermeneutical phenomenology, which conducted in-depth semi-structured interviews with people trained on the irritable bowel syndrome. The sampling was intentional type and open questions were used to collect data. The Thematic Analysis Method by Van Manen was used. Results. Two principal themes and five subthemes emerged in this research to determine the meaning of living with the irritable bowel syndrome: Storm in corporality (body with pain and affliction, tension and sequence of symptoms, and: distress during moments of life) and Relief (sense of liberation of the body symptoms, and moments with pleasure). Conclusion. The experience lived by patients with irritable bowel syndrome is of a transitory crisis and liberation. How to cite this article: Mohebbi Z, Sharif F, Peyrovi H, Rakhshan M, Naini MA, Zarshenas L. Experience Lived by Iranian Patients with Irritable Bowel Syndrome: Transitory Crisis and Liberation. Invest. Educ. Enferm. 2019; 37(3):e10.